Impact of combined intermittent preventive treatment of malaria and helminths on anaemia, sustained attention, and recall in Northern Ghanaian schoolchildren. Issue 1 (1st December 2016) - Opoku, Ernest Cudjoe; Olsen, Annette; Browne, Edmund; Hodgson, Abraham; Awoonor-Williams, John K.; Yelifari, Lawrence; Williams, John; Magnussen, Pascal
Abstract : Background: The benefits of integrated control of malaria, schistosomiasis, and soil-transmitted helminth infections have not been fully explored in Ghanaian schoolchildren. Objective: To assess the impact of co-administered artemether-lumefantrine plus albendazole, and artemether-lumefantrine plus albendazole plus praziquantel compared to albendazole plus praziquantel on anaemia, sustained attention, and recall in schoolchildren. Design: This three-arm, open-label intervention study was carried out in Ghana among class three schoolchildren. Artemether-lumefantrine and albendazole were co-administered to 131 schoolchildren in Study Arm 1; artemether-lumefantrine, albendazole, and praziquantel to 90 children in Study Arm 2 versus albendazole and praziquantel to 127 children in Control Arm 3. Medicines were administered to all children at least 30 min after a meal. A HemoCue ® photometer was used to measure haemoglobin (Hb), while the code transmission test (CTT), adapted from the Test of Everyday Attention for Children (TEA-Ch), was used to measure sustained attention and recall before-and-after interventions in June 2011 and June 2012. Results: We observed significant malaria parasite prevalence reductions of 62.8 and 59.2% in Study Arm 1 from 24.2 to 9.0%, p< 0.01, and 59.2% in Study Arm 2 from 26.7 to 10.9%, p< 0.01), respectively, compared to 8.93% in Control Arm 3 (from 34.7 to 31.6%, p> 0.05). Meanwhile, anaemia prevalence reduced significantly ( p <0.01) in all three study arms after interventions by 38.4% (from 19.8 to 12.2%), 20.7% (from 26.6 to 21.1%), and 36.0% (from 28.3 to 18.1%) in Study Arms 1, 2, and 3, respectively. Although the interventions had no significant effects on Hb levels, anaemia prevalence reduced insignificantly by 38.4 and 20.7% in Study Arms 1 and 2, respectively, compared to 36.0% in Control Arm 3. Among schoolchildren in Study Arms 1 and 2, mean CTT score improved significantly after interventions by 10.4% (from 3.18 to 3.55, p =0.01) and 20.5% (from 2.83 to 3.56, p =0.01) respectively, compared to 5.75% in Control Arm 3 (from 2.95 to 3.13, p =0.09). Likewise, mean recall test score improvements after interventions were 16.9% (from 2.07 to 2.49, p =0.01) and 27.9% (from 1.91 to 2.65, p =0.01) in Study Arms 1 and 2, respectively, compared to 18.3% (from 1.92 to 2.35, p =0.01) in Control Arm 3. Conclusion: Combined intermittent preventive treatment of malaria and deworming reduced prevalence of anaemia and improved sustained attention and recall in schoolchildren. Best results for sustained attention and recall were seen in Study Arm 2.